Inclusive Education and ELT Policies in Colombia: Views From Some PROFILE Journal Authors (2017)
This article reports on a study aimed at exploring inclusive policies in the teaching of English as a foreign language in Colombia, as evidenced in the articles published in the PROFILE Journal by Colombian authors. The use of the documentary research method and critical discourse analysis showed that some policies—mainly The National Program of Bilingualism and the Basic Standards for Competences in English as a Foreign Language—contain issues closely related to the logic of discriminatory and segregation attitudes in English language teaching. We hope that the results of our analysis will generate more interest in scholars to examine language policies and work further to eradicate inequalities in education.